AIS-Based Estimation of Hydrogen Demand and Self-Sufficient Fuel Supply Systems for RoPax Ferries - Annika Christine Fitz; Juan Camilo Gómez Trillos; Frank Sill Torres (Energies, 2022)
The International Maritime Organization (IMO) established new strategies that could lead to a significant reduction in the carbon footprint of the shipping sector to address global warming. A major factor in achieving this goal is transitioning to renewable fuels. This implies a challenge, as not only ship-innovative solutions but also a complete low-carbon fuel supply chain must be implemented. This work provides a method enabling the exploration of the potential of low-carbon fuel technologies for specific shipping routes up to larger sea regions. Several aspects including vessel sizes, impact of weather and shipping routes, emissions savings and costs are considered. The local energy use is determined with proven bottom-up prediction methods based on ship positioning data from the Automatic Identification System (AIS) in combination with weather and ship technical data. This methodology was extended by an approach to the generation of a basic low-carbon fuel system topology that enables the consideration of local demand profiles. The applicability of the proposed approach is discussed at hand via a case study on Roll-on/Roll-off passenger and cargo (RoPax) ferries transitioning from conventional fuels to a compressed hydrogen fuel system. The results indicate a potential reduction in emissions by up to 95% and possible system sizes and costs.